Analisis Pengaruh Penerbitan Sukuk terhadap Abnormal Return Perusahaan di Indonesia - Riska Permatalia; Muhammad Istan (Politeknik Negeri Batam, 2020)
This study aimed to analyze the effect of sukuk issuance on abnormal returns of companies in Indonesia. The companies issued sukuk on the sharia’s capital market as an alternative to additional funds for production and distribution. This was expected to increase profits and affect companies’ stock price to drive investors. This study used descriptive quantitative method with data sourced from companies of 2019’s Indonesia Stock Exchange (IDX) covering 68 samples. Analyses deployed statistical tests, classical assumption tests, and multiple linier regression to test market reactions to sukuk issuance on the issuance value, maturity date, company leverage, total assets, and rating. Results affecting abnormal returns were sukuk maturity date at α 5% and total assets at α 10%. Concerning the value of sukuk issuance, company leverage, and rating, there were no significant effects on abnormal returns. This demonstrated that the information needed by investors had not been fulfilled.